Effect of Se diffusion and the role of a thin CdS buffer layer in the performance of a CdSe/CdTe solar cell. (September 2019) - Reyes-Banda, Martín G.; Regalado-Perez, E.; Pintor-Monroy, M.I.; Hernández-Gutiérrez, C.A.; Quevedo-López, M.A.; Mathew, X.
Abstract: In this work the beneficial aspects of substituting CdS, the traditional heterojunction partner to CdTe, with a bi-layer of CdSe/CdS is studied and the results are discussed. The high short-circuit current in a CdTe/(CdSe/CdS) solar cell is mainly due to contribution from two factors; enhanced blue-response due to the reduction in CdTe band gap which a result of Se diffusion into CdTe film forming the ternary CdTe1-x Sex at the interfacial region, and the use of a thinner CdSe layer which was possible due to the presence of a thin CdS film. A thin layer of CdS between indium-tin-oxide (ITO) and CdSe is essential to serve as a buffer layer minimizing the shunt paths at the heterojunction interface. A 10% increase in short-circuit current is observed when the CdS-alone heterojunction layer is substituted with a CdSe/CdS bi-layer. The SIMS depth profile analysis indicate that in devices using a CdSe/CdS bi-layer, the Cu diffusion from back contact into the CdTe bulk is limited significantly compared to a CdS-only device. The net carrier concentration across the absorber layer is not uniform and showed the characteristic U-shape with respect to depletion layer width. The apparent increase in carrier concentration near the back contact region is related to the Cu doping. The shallow vs. sharp curving of the NA -ND profile of the CdS-only and CdSe/CdS bi-layer devices is explained on the basis of the regulated Cu diffusion from the back contact into CdTe, which is a consequence of Se diffusion. Graphical abstract: Image 1 Highlights: A thin CdS layer enhances blue response while CdSe is consumed due to Se diffusion Se regulates Cu diffusion from back contact and hence the carrier concentration Exist an inverse relation between carrier concentration and CdSe film thickness. Discrepancy about the role of the CdS/CdSe bilayer is investigated.